2009
DOI: 10.1021/pr900414f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Plasma Peptidome from Pancreas Cancer Patients Connects a Peptide in Plasma to Overexpression of the Parent Protein in Tumors

Abstract: Blood circulates through nearly every organ including tumors. Therefore, plasma is a logical source to search for tumor-derived proteins and peptides. The challenge with plasma is that it is a complex bodily fluid composed of high concentrations of normal host proteins that obscure identification of tumor-derived molecules. To simplify plasma, we examined a low molecular weight (LMW) fraction (plasma peptidome) using liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods. In the plasma peptidome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 49 publications
3
68
0
Order By: Relevance
“…Other comparisons including lists of endogenous plasma peptides 21 and other proteins showed similar results. In addition, none of these lists include any post-translational modifications (PTMs), and only recently a few phosphorylated endogenous serum peptides were reported 22 .…”
Section: Maldi and Esi Ms/ms Analysis Of Some Of The Maldi Ms Profilisupporting
confidence: 61%
“…Other comparisons including lists of endogenous plasma peptides 21 and other proteins showed similar results. In addition, none of these lists include any post-translational modifications (PTMs), and only recently a few phosphorylated endogenous serum peptides were reported 22 .…”
Section: Maldi and Esi Ms/ms Analysis Of Some Of The Maldi Ms Profilisupporting
confidence: 61%
“…Recently, a number of reports have analyzed the half-life and overall stability of peptides in biological fluids and shown that most peptides are bound to carrier proteins, including albumin, lipoproteins, immunoglobulins, and transthyretin. The peptides exist in equilibrium between their free and bound form, and their half-life varies between 1 and 20 days, directly proportional to the half-life of the carrier protein (3,25). The prolonged half-life and continuing production of these carrierbound peptides support an available amount of biological fluids far superior to the steady-state concentration of free peptide.…”
Section: Peptide Sourcementioning
confidence: 99%
“…Conventional dendritic cells (cDC) 3 are a heterogeneous population of antigen-presenting cells involved in different aspects of tolerogenic and immunogenic T cell responses. They are subclassified as resident cDC, which reside in secondary lymphatic organs (spleen and lymph node), and migratory cDC, which traffic from peripheral tissues to the draining lymph nodes and the thymus (30 -33).…”
mentioning
confidence: 99%
“…These results were confirmed by western blotting, suggesting that these markers may be useful adjuncts to the existing biomarkers, CA19-9 and CEA. Despite using similar methods, another study reported the presence of a peptide chain from sulphhydryl oxidase 1 as their only significant finding and linked this to the expression of protein in pancreatic tumour cell lines (Antwi et al 2009). These studies highlight the fact that proteomic research using MS/MS can yield very variable results even though the methodology may be similar.…”
Section: Mass Spectrometry and Pancreatic Tumoursmentioning
confidence: 99%